VC: Stand up & be heard - UMP, PNC
Universiti Malaysia Pahang (UMP) Vice-Chancellor, Professor Dato’ Dr Daing Nasir Daing Ibrahim, has called upon UMP students to take advantage of the availed opportunities to voice their concerns and to be heard.